Evolution and genetic architecture of disassortative mating at a locus under heterozygote advantage. (13th December 2020) - Maisonneuve, Ludovic; Chouteau, Mathieu; Joron, Mathieu; Llaurens, Violaine
Abstract: The evolution of mate choice is a major topic in evolutionary biology because it is thought to be a key factor in trait and species diversification. Here, we aim at uncovering the ecological conditions and genetic architecture enabling the puzzling evolution of disassortative mating based on adaptive traits. This rare form of mate choice is observed for some polymorphic traits but theoretical predictions on the emergence and persistence of this behavior are largely lacking. Thus, we developed a mathematical model to specifically understand the evolution of disassortative mating based on mimetic color pattern in the polymorphic butterfly Heliconius numata . We confirm that heterozygote advantage favors the evolution of disassortative mating and show that disassortative mating is more likely to emerge if at least one allele at the trait locus is free from any recessive deleterious mutations. We modeled different possible genetic architectures underlying mate choice behavior, such as self‐referencing alleles, or specific preference or rejection alleles. Our results showed that self‐referencing or rejection alleles linked to the color pattern locus enable the emergence of disassortative mating. However, rejection alleles allow the emergence of disassortative mating only when the color pattern and preference loci are tightly linked.